Pengaruh Edukasi Kesehatan Pemberian Kolostrum pada Ibu Hamil Trimester III terhadap Peningkatan Pemberian Kolostrum pada Bayi Baru Lahir - Desna Syafira Berliana Putri; Mudy Oktiningrum; Eddy Wibowo (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Colostrum is the first natural food for newborns, containing essential nutrients and antibodies that protect against infection. Health education for pregnant women in their third trimester is crucial to enhance their knowledge and practices regarding colostrum provision. Despite the global decline in neonatal mortality, the rate remains high, partly due to limited access and low quality of neonatal care. In Indonesia, particularly in Semarang, although exclusive breastfeeding coverage has improved, many mothers still lack understanding of colostrum’s importance and remain influenced by misconceptions. Preliminary studies revealed insufficient knowledge among pregnant women about colostrum. Method: This study applied a quasi-experimental method with a pretest-posttest design and a control group. The intervention group received health education, while the control group did not. Results: Before intervention, most respondents in both groups had poor knowledge. After the intervention, knowledge in the intervention group increased significantly, with 88.8% reaching a good category, while the control group showed no significant change. Furthermore, 94.4% of mothers in the intervention group gave colostrum, compared with only 33.3% in the control group. Conclusion: Health education is an effective strategy to increase maternal knowledge and encourage colostrum practice, dispelling myths and promoting better neonatal outcomes.